Pengaruh Budaya Organisasi dan Pengalaman Kerja Terhadap Kinerja Karyawan LPD se-kecamatan Buleleng - Kadek Ayu Nopiani; Luh Indrayani (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2026)
This study aimed to determine the influence of organizational culture and work experience on employee performance in LPDs throughout Buleleng District, both partially and simultaneously. The design used in this study was a causal associative approach. The subjects were LPDs throughout Buleleng District, and the objects of the study were organizational culture, work experience, and employee performance. The data used were primary and secondary data analyzed using classical assumption testing and multiple linear regression analysis. The results showed that organizational culture had a partial negative effect on employee performance with a significance value of 0.000 < 0.05, and work experience had a negative effect on employee performance with a significance value of 0.035 < 0.05. Simultaneously, organizational culture and work experience had a significant effect on employee performance.